2012
DOI: 10.5376/ijms.2012.02.0001
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual Variability of Chlorophyll-a in the Arabian Sea and its Gulfs

Abstract: The analysis of chlorophyll-a for a 7 year period from the ocean color images of SeaWiFS in the Arabian Sea and its marginal seas showed considerable inter-annual and geographical variability. The variability in chlorophyll-a was essentially centered on the Southwest and the Northeast monsoon seasons. The mean seasonal chlorophyll-a of the Northeast Monsoon in the western Arabian Sea showed an increasing trend from 1998 to 2004. The period of elevated chlorophyll-a levels in the Gulf of Mannar is apparently ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In boreal winter, convective overturning allows entrainment of nutrients into the mixed layer and leads to a prominent bloom in the northern AS (Banse and English, 2000;Madhupratab et al, 1996;Prasanna Kumar et al, 2001;Wiggert et al, 2002). In addition to these seasonal variations, several studies have revealed large interannual variations in the AS winter chlorophyll from either satellite (Banse and McClain, 1986;Banse and English, 1993;Sarma et al, 2006Sarma et al, , 2012Wiggert et al, 2002) or in situ measurements (Bauer et al, 1991;Madhupratap et al, 1996;Gundersen et al, 1998;Prasanna Kumar et al, 2001). This strong interannual variability of the northern AS winter bloom is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In boreal winter, convective overturning allows entrainment of nutrients into the mixed layer and leads to a prominent bloom in the northern AS (Banse and English, 2000;Madhupratab et al, 1996;Prasanna Kumar et al, 2001;Wiggert et al, 2002). In addition to these seasonal variations, several studies have revealed large interannual variations in the AS winter chlorophyll from either satellite (Banse and McClain, 1986;Banse and English, 1993;Sarma et al, 2006Sarma et al, , 2012Wiggert et al, 2002) or in situ measurements (Bauer et al, 1991;Madhupratap et al, 1996;Gundersen et al, 1998;Prasanna Kumar et al, 2001). This strong interannual variability of the northern AS winter bloom is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%